Hikikomori: Review on a severe phenomenon of social withdrawal - Domingues-Castro, Mariana S. [UNESP]; Torres, Albina R. [UNESP] (FapUNIFESP (SciELO), 2018)
Objectives: To expand the current knowledge on the phenomenon of severe, voluntary and prolonged social withdrawal called hikikomori, and to facilitate the identification and treatment of these individuals. Methods: A comprehensive review of the literature from 2000 to 2017 has been conducted, using several data bases as search instruments using the keywords “hikikomori”, “youth social withdrawal” and “prolonged social isolation”. Results: Hikikomori was firstly described in Japan and was considered a culture-bound syndrome. However, in the last years, it has been described in several other countries, including western countries. It affects mainly male adolescents and young adults, who spontaneously live recluse in their rooms, for at least six months. They are lonely and shy people, with insufficient social support, who frequently had some traumatic experience in childhood. Most of them present some associated psychiatric disorder. The phenomenon leads to terrible losses to the individuals, their families and to society. Conclusion: Hikikomori is an underdiagnosed and undertrea-ted condition outside Japan, due to the lack of knowledge of health professionals, and for the sufferers’ refusal to seek help. The phenomenon was not yet included as a psychiatric disorder in the classifications, what difficults the standardization and conduction of research around the world.
Hikikomori: Revisão sobre um grave fenômeno de isolamento social
Keywords: Hikikomori; Prolonged social isolation; Youth social withdrawal